Optimizing Agricultural Yield and Supply Chain via Client-Server Architecture - Kusuma, Alif Arya; Zaky, Umar (Kirana Publisher (KNPub), 2025)
The agricultural sector in developing regions often faces dual challenges: the lack of systematic harvest data recording and inefficient supply chains dominated by intermediaries. These issues result in suboptimal land productivity management and reduced profit margins for farmers. This study addresses these problems by designing a system based on Client-Server Architecture to digitize harvest records and facilitate direct-to-partner transactions. Utilizing Flutter as the mobile client and Laravel as the server-side API provider backed by PostgreSQL, the system implements a specific Land Productivity Yield (LPY) algorithm to map high-performing cultivation methods. The architecture connects three strategic stakeholders: Farmers, Regional Coordinators, and Industrial Partners. Usability testing using the System Usability Scale (SUS) yielded a score of 79.25, indicating high acceptance among the user demographic. The results demonstrate that the proposed architecture successfully reduces information asymmetry and provides a robust framework for data-driven decision-making in regional agriculture.